Top performer : a bold approach to sales and service - Lundin, Stephen C., 1941-; Hagerman, Carr, 1958- (New York : Hyperion AudioBooks, 2006)
In a business parable, the Rat Catcher, a Dublin street performer, offers a valuable lesson to Jim, a disciplined but uninspired sales manager, on how to harness his natural energy to take personal satisfaction and job motivation to the next level
Read by Carr Hagerman
Keywords: Selling; Audiobooks